Vaccination coverage of patients with inborn errors of metabolism and the attitudes of their parents towards vaccines. Issue 48 (27th November 2015) - Cerutti, Marta; De Lonlay, Pascale; Menni, Francesca; Parini, Rossella; Principi, Nicola; Esposito, Susanna
Highlights: Infectious diseases place patients with IEMs at high risk of metabolic decompensation. Vaccines could play a relevant role in treatment of IEMs patients. Patients with IEM demonstrate sub-optimal vaccination rates. An increase in physician knowledge of the vaccine's benefits and safety issues is extremely important. Educational programmes are urgently needed to increase immunization coverage in patients with IEMs. Abstract: To evaluate vaccination coverage of children and adolescents with inborn errors of metabolism (IEMs) and the attitudes of their parents towards vaccination, the vaccination status of 128 patients with IEM and 128 age- and gender-matched healthy controls was established by consulting the official vaccination chart. In children with IEMs, compared with healthy controls, low vaccination rates and/or delays in administration were observed for pneumococcal conjugate, meningococcus C, measles, mumps, rubella, diphtheria-tetanus-pertussis-inactivated polio, Bacillus Calmette–Guerin, and influenza vaccines. Among the parents of IEM patients, vaccine schedule compliance was primarily driven by the doctors at the hospital's reference centres; among the parents of the healthy controls, compliance was driven by the primary care paediatricians. These results show that IEM patients demonstrate sub-optimal vaccination coverage. Further studies of the different vaccines in each IEM disorder and educational programmes aimed at physicians and parents to increase immunization coverage in these patients are urgently needed.